EVALUASI IMPLEMENTASI MANAJEMEN PEMERINTAHAN DESA DI KECAMATAN PURWOREJO KABUPATEN PURWOREJO - Wahyu Purhantara (Jurnal Penelitian Humaniora, 2010)
Management of local sometimes does not work in maximum as expected. Local government never succeeds in increasing performance and public services. This condition is caused by the lack of local government employees understanding and capability, which cover: understanding and capability of the job, function, competence of local government chairman and BPD that is not responsive to the changing need of the society. The aim of this study is to recognize the effectiveness of local government implementation and the barriers faced. The type of this study is qualitative descriptive using data collecting method, including observation and interviews. Population in this study is all employees engaged in government activities. The result of the analyses shows that the level of local government activities have not worked in maximum, especially in coordination activities and its evaluation. Meanwhile coordination in other areas have not worked optimally, such as coordination in planning, controlling program, and evaluating the result of local development.